1990
DOI: 10.1002/j.1460-2075.1990.tb07590.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of replication of plasmid R1: structures and sequences of the antisense RNA, CopA, required for its binding to the target RNA, CopT.

Abstract: The replication frequency of plasmid R1 is determined by the availability of the RepA protein, which acts at the origin of replication to promote initiation. Synthesis of RepA is negatively regulated both at the transcriptional and post‐transcriptional levels. Post‐transcriptional control is exerted through the action of an antisense RNA, CopA RNA. The target of CopA RNA, CopT RNA, is located in the leader region of the RepA mRNA. Binding between CopA and CopT inhibits repA expression. We have previously prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 41 publications
4
84
0
Order By: Relevance
“…We showed previously that full CopA-CopT duplexes are only slowly formed in vitro, and identified a stable complex using double-strand-specific enzyme RNase III-and Pb 2ϩ -catalyzed cleavages (Malmgren et al+, 1997)+ To obtain detailed structural information about the CopA-CopT complex, we used a range of enzymes and chemical reagents+ To study the extended kissing complex, CopA was replaced by the truncated CopA variant CopI, which contains only the major stem-loop structure (Persson et al+, 1990a) (Chen et al+, 1993) and DEPC (Weeks & Crothers, 1993) are known to be very sensitive to stacking of base rings+ Therefore, position N7 of purines within a helix is not reactive unless the deep groove is widened+ RNAs were also subjected to Pb 2ϩ -induced cleavage, which has proven exquisitely sensitive to subtle structural variations (Malmgren et al+, 1997 CopA-CopT complexes were formed at 37 8C for 2-15 min and subjected to enzymatic cleavages or chemical modifications+ We previously showed that within 15 min of incubation, at given concentrations, most RNAs were in the form of stable complexes, but only a minor fraction was converted to a full duplex (Malmgren et al+, 1997 Structure mapping of the complexes formed by CopICopT and CopA-CopT supported the presence of two intermolecular helices, B and B9, as modules in the four-helix junction structure (Fig+ 6)+ To delimitate the number of base pairs in the two intermolecular helices, we used site-directed mutagenesis of the copA/copT gene sequence+ Base-pair inversions were introduced at three positions within stem II+ These mutations affect neither the stability nor the structure of the RNAs in their free state (data not shown), but were expected to affect formation of helices B and B9 (Fig+ 6)+ Polymerase chain reaction (PCR)-generated templates were used for transcription of mutated CopI, CopA, and CopT Cleavages by RNase V1 was used to obtain a signature of the extended kissing complex: new or enhanced cleavages were induced in CopA or CopI at consecutive positions U52-C56, and in CopT at C104-A105+ Furthermore, in the CopA-CopT complex, the formation of the intermolecular helix C that greatly enhances complex stability was characterized by several V1 cuts in CopT at U162-C163 and U167-A168, as well as by the disappearance of V1 cleavages in CopA at positions G7-A9 and G16-A19, resulting from melting of helix I+ Therefore, we used RNase V1 to probe the structure of the homologous and heterologous complexes formed with the H1, H2, and H3 RNA variants (Fig+ 5)+ In all these experiments, we used conditions (RNA concentrations, time of incubation, buffers) under which the stable CopA-CopT complex is almost quantitatively formed+ RNase V1 probing of end-labeled CopA RNA variants indicated almost identical cleavage patterns of free mutant and wild-type RNAs+ Hence, no major structural changes were caused by the mutations+ The three homologous CopA/CopT and the heterologous CopA-H3/ CopT-wt complexes showed the characteristic RNase V1 patterns, that is, the appearance of cleavages at positions U52-C56 in CopA (Fig+ 5A)+ Interestingly, the heterologous complexes formed between CopT-wt and either CopA-H1 or CopA-H2 were different: significant protections were observed at U49-C50 of CopA-H1 and CopA-H2 (Fig+ 5A), whereas positions U52-C56 remained uncleaved, that is, a pattern resembling that of free RNAs+ The same experiments were also performed using end-labeled CopT variants (Fig+ 5B)+ Again, no major structural changes occurred in CopT mutant RNAs, and identical cleavage patterns were observed for all homologous CopA-CopT complexes, as well ...…”
Section: Enzymatic and Chemical Probing Of The Antisense And Target Rnasmentioning
confidence: 99%
See 3 more Smart Citations
“…We showed previously that full CopA-CopT duplexes are only slowly formed in vitro, and identified a stable complex using double-strand-specific enzyme RNase III-and Pb 2ϩ -catalyzed cleavages (Malmgren et al+, 1997)+ To obtain detailed structural information about the CopA-CopT complex, we used a range of enzymes and chemical reagents+ To study the extended kissing complex, CopA was replaced by the truncated CopA variant CopI, which contains only the major stem-loop structure (Persson et al+, 1990a) (Chen et al+, 1993) and DEPC (Weeks & Crothers, 1993) are known to be very sensitive to stacking of base rings+ Therefore, position N7 of purines within a helix is not reactive unless the deep groove is widened+ RNAs were also subjected to Pb 2ϩ -induced cleavage, which has proven exquisitely sensitive to subtle structural variations (Malmgren et al+, 1997 CopA-CopT complexes were formed at 37 8C for 2-15 min and subjected to enzymatic cleavages or chemical modifications+ We previously showed that within 15 min of incubation, at given concentrations, most RNAs were in the form of stable complexes, but only a minor fraction was converted to a full duplex (Malmgren et al+, 1997 Structure mapping of the complexes formed by CopICopT and CopA-CopT supported the presence of two intermolecular helices, B and B9, as modules in the four-helix junction structure (Fig+ 6)+ To delimitate the number of base pairs in the two intermolecular helices, we used site-directed mutagenesis of the copA/copT gene sequence+ Base-pair inversions were introduced at three positions within stem II+ These mutations affect neither the stability nor the structure of the RNAs in their free state (data not shown), but were expected to affect formation of helices B and B9 (Fig+ 6)+ Polymerase chain reaction (PCR)-generated templates were used for transcription of mutated CopI, CopA, and CopT Cleavages by RNase V1 was used to obtain a signature of the extended kissing complex: new or enhanced cleavages were induced in CopA or CopI at consecutive positions U52-C56, and in CopT at C104-A105+ Furthermore, in the CopA-CopT complex, the formation of the intermolecular helix C that greatly enhances complex stability was characterized by several V1 cuts in CopT at U162-C163 and U167-A168, as well as by the disappearance of V1 cleavages in CopA at positions G7-A9 and G16-A19, resulting from melting of helix I+ Therefore, we used RNase V1 to probe the structure of the homologous and heterologous complexes formed with the H1, H2, and H3 RNA variants (Fig+ 5)+ In all these experiments, we used conditions (RNA concentrations, time of incubation, buffers) under which the stable CopA-CopT complex is almost quantitatively formed+ RNase V1 probing of end-labeled CopA RNA variants indicated almost identical cleavage patterns of free mutant and wild-type RNAs+ Hence, no major structural changes were caused by the mutations+ The three homologous CopA/CopT and the heterologous CopA-H3/ CopT-wt complexes showed the characteristic RNase V1 patterns, that is, the appearance of cleavages at positions U52-C56 in CopA (Fig+ 5A)+ Interestingly, the heterologous complexes formed between CopT-wt and either CopA-H1 or CopA-H2 were different: significant protections were observed at U49-C50 of CopA-H1 and CopA-H2 (Fig+ 5A), whereas positions U52-C56 remained uncleaved, that is, a pattern resembling that of free RNAs+ The same experiments were also performed using end-labeled CopT variants (Fig+ 5B)+ Again, no major structural changes occurred in CopT mutant RNAs, and identical cleavage patterns were observed for all homologous CopA-CopT complexes, as well ...…”
Section: Enzymatic and Chemical Probing Of The Antisense And Target Rnasmentioning
confidence: 99%
“…The overall topology structure of the extended kissing complex is similar to some other RNA four-way junctions (Krol et al+, 1990;Walter et al+, 1998a;Nowakowski et al+, 1999) and DNA Holliday junctions (Duckett et al+, 1992)+ In both DNA and RNA four-way junctions, divalent ions are required for the formation and stabilization of antiparallel X-shaped structures (Duckett et al+, 1992;Walter et al+, 1998b)+ The particularity of the proposed CopA-CopT structure is the crossing over of the strands at the junction under the constraints imposed by the two loops connecting intermolecular helices B and B9+ This forces a side-by-side alignment of the two helical domains that brings the 59 tail of CopA in close proximity to the complementary region of CopT (Fig+ 7)+ The formation of intermolecular helix C, which clamps the two long helical domains, greatly enhances the stability of the complex (Persson et al+, 1990a;Malmgren et al+, 1997)+ Crystallographic analysis of a group I ribozyme domain revealed a similar organization (Cate et al+, 1996): a sharp bend induced by an internal loop allows a side-by-side alignment of two helical domains that is additionally stabilized by metal-and ribosemediated backbone contacts and two long-range tertiary interactions+ A side-by-side configuration was also proposed for the hairpin ribozyme, here stabilized by interactions between two internal loops (Earnshaw et al+, 1997)+ The formation of a stable RNA-RNA complex is not unique to CopA-CopT, and is also a key feature in the replication control of plasmids belonging to the IncB and IncIa groups (Siemering et al+, 1994; plasmids+ In these systems, the antisense RNAs inhibit the formation of a pseudoknot structure that activates rep translation (Wilson et al+, 1993;)+ All these antisense and target RNAs are characterized by stable hairpins with identical loop sequences and bulged residues in the upper stem regions+ Enzymatic probing performed on (antisense) RNAI in pMU720 plasmid bound to its target indicated that a full duplex was not rapidly formed in vitro+ Instead, binding resulted in an extended kissing complex stabilized by 59 tail interactions (Siemering et al+, 1994)+ One may therefore speculate that, in all these systems, the final product of the binding reaction in vitro is characterized by an overall topology very similar to that reported here, except that the lengths of helices B and B9, if formed in the IncB/IncIa cases, could be different+…”
Section: Conversion Of a Loop-loop Interaction To A Four-helix Junctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondary structures of tRNA leu amber suppressor (A), aptamer 1 (B), and aptamer 2 (C), represented as a tRNA-like molecule+ Under each aptamer the linear sequences corresponding to the anticodon loop of the suppressor tRNA are aligned with the corresponding sequences of the aptamer+ Complementary sequences are indicated in bold+ tRNA suppressor inhibition 905 complementary to the anticodon loop of the suppressor are flanked by sequences one would expect not to pair; the 5 nt at the 39 end are also complementary to the 59 half of the anticodon stem of the suppressor (Fig+ 1C)+ When the loops of aptamer 2 and of the suppressor interact, the 39 part of the aptamer's stem is free to base pair with the 59 part of the suppressor's stem; the aptamer-suppressor transitory coupling can lead to the formation of a more stable 12-bp interaction (Persson et al+, 1990;Zeiler & Simons, 1998)+ We cloned both aptamer 1 and 2 into pGFIB-I (Normanly et al+, 1986(Normanly et al+, , 1990)+ In this high-copy number plasmid that encodes an ampicillin-resistant gene, each aptamer is constitutively expressed from a strong synthetic promoter based on the constitutive promoter sequence of the E. coli lipoprotein gene lpp+ Distal to the promoter and restriction site polylinker is a transcription terminator, corresponding to the termination sequence of the ribosomal RNA operon rrnC+…”
Section: Construction Of the Aptamersmentioning
confidence: 99%